Analyzing The Effect of Alternative Banking Channels on the Employees Productivity of the Commercial Banks: Evidence from the State Bank of India - Shrivastava, Geetanjali; Adwani, Vinod Kumar; Vaydande, Neeta (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Alternative Banking Channel is a branchless access channel to banking institutions at a lower cost, convenience, high subscription rate, faster transaction speed, and expanded income sources. The purpose of this study is to look on the other side also i.e. the productivity of the employees. For the study, State Bank of India has been selected (largest Public Sector Bank of India). Only secondary sources such as annual reports, published publications, conference papers, books, and banking websites were used to obtain the data. With the help of regression model, an attempt has been made to analyze the impact of alternative banking channels on the productivity of SBI’s employees. According to this research, the rate of use of ABC products such as Online Banking, ATM Card, POS, Internet Banking, Mobile-Cash, Electronic Fund Transfer, and Real-Time Gross Settlement is increasing which has not only boosted the profitability of SBI but also increased the Business productivity of employees.